2011
DOI: 10.1080/10426507.2010.524174
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Thiofenchone or Thiochamphor with Disulfur Dichloride: Novel Formation of Tricyclic Polysulfanes

Abstract: Reaction of thiofenchone with disulfur dichloride gave trisulfane (15%) and tricyclic tetrasulfane (50%), all of which were Wagner-Meerwein rearranged products. Thiocamphor also reacted with disulfur dichloride to afford six-and seven-membered tricyclic polysulfanes. Selenofenchone also reacted with diselenium dibromide to afford diselenane and triselenane, both of which were Wagner-Meerwein rearranged products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, trisulfide 49 is known to form in the reaction of thioketone 50 with S 2 Cl 2 (Scheme 31). 50 The highest yield of the product (66%) has been achieved in the reaction catalyzed by trifluoroacetic acid. It should be noted that neither strong evidence of the structure of trisulfide 49 nor explanations of the mechanism of its formation have been reported.…”
Section: Compounds With Three Sulfur Atomsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, trisulfide 49 is known to form in the reaction of thioketone 50 with S 2 Cl 2 (Scheme 31). 50 The highest yield of the product (66%) has been achieved in the reaction catalyzed by trifluoroacetic acid. It should be noted that neither strong evidence of the structure of trisulfide 49 nor explanations of the mechanism of its formation have been reported.…”
Section: Compounds With Three Sulfur Atomsmentioning
confidence: 97%
“…This product is a result of a complex sequence of transformations, involving the S 2 Cl 2 attack, the Wagner ± Meerwein rearrangement and cyclization of compound 206 to tetrathiepane (Scheme 103). 50 Benzodithiastannoles have been early known as promising precursors in synthesis of fused 1,2,3,4,5-pentathiepins; three sulfur atoms are introduced with the use of sulfur monochloride (see Section III.3). Recently, it has been shown that carrying out the reaction at low temperature in tetrahydrofuran allows the reaction to be stopped after the formation of benzo-1,2,3,4-tetrathiane.…”
Section: Scheme 102mentioning
confidence: 99%